Global burden of metabolic-associated fatty liver disease among women of childbearing age: Trends from 1990 to 2021 and projections to 2040 - Jiaxing Li; Qihui Hu; Jiajie Leng; Baoyong Zhou; Cong Chen; Yaoyue Hu; Bingdi Chao; Zhenhao Huang; Zhenrui Cao; Zhongling An; Jixing Wang; Dingheng Hu; et al. (PLoS ONE, 2025)
Background Metabolic-associated fatty liver disease (MAFLD) is a growing global health concern, particularly among women of childbearing age (WCBA). We aimed to analyze the global burden of MAFLD among WCBA from 1990 to 2021 and project trends to 2040. Methods Data on incidence, prevalence, deaths, and disability-adjusted life years (DALYs) were extracted from the Global Burden of Disease Study 2021. Joinpoint regression and decomposition analysis were used to assess historical trends, and Bayesian Age-Period-Cohort (BAPC) modeling projected future burdens. Results From 1990 to 2021, the age-standardized rate (ASR) of MAFLD incidence and prevalence among WCBA increased globally (EAPC = 0.76 and 0.71, respectively). China showed declining trends in deaths (EAPC = −2.63) and DALYs (EAPC = −2.62). By 2040, BAPC modeling predicts a continued rise in global incidence and prevalence, with regional disparities in mortality. Population growth was the primary driver of the global increase in MAFLD incidence, accounting for 63.38% of the rise. Conclusion MAFLD imposes a significant burden on WCBA globally, with socioeconomic disparities driving regional variations. Targeted interventions addressing obesogenic environments and healthcare inequities are urgently needed.